PARASITISASI Diadegma semiclausum Hellen (HYMENOPTERA: ICHNEUMONIDAE) PADA HAMA Plutella xylostella (LEPIDOPTERA; PLUTELIDAE) DI TOMOHON - Michael S.N. Bakri; Moulwy F. Dien; Daisy S. Kandowangko (COCOS, 2015)
ABSTRACT Â Cabbage moth (diamondback moth), Plutella xylostella (Lepidoptera: Plutellidae) is a major pest that is very damaging on plant family Brassicaceae, especially cabbage plants. The study aims to determine parasitation P. xylostella in cabbage planting and Brassiscae area in Tomohon. This study uses survey at four locations in Tomohon, namely Rurukan village, Kumelembuay village, Wailan village and Kakaskasen Two village. Results of the study was only found one type of parasitoids that attack Plutella xylostella in the Tomohon city. Identification results showed that parasitoids that attack the larvae / pupae of P. xylostella is Diadegma semiclausum. The average percentage of parazitation D. semiclausum against P. xylostella in Tomohon highest found in location of Rurukan village (82.01%), Kumelembuay village (76.58%), Wailan village (73.37%) and the lowest in the Kakaskasen Two village (71.94%). Â Key word : Cabbage, Plutella xylostella, Diadegma semiclausum